Youth Football Players’ Psychological Well-Being: The Key Role of Relationships - Reverberi, Eleonora; D’Angelo, Chiara; Littlewood, Martin A.; Gozzoli, Caterina Francesca (Frontiers in Psychology, 2020)
The work examines the influence of the relationship that football players have with significant others on their psychological wellbeing (PWB), adopting a psychosocial perspective. According to this perspective, PWB can be considered a basic condition for an effective talent development and holistic growth of young athletes. Current literature on talent development in sport has been analyzed to support the theoretical hypothesis of psychosocial perspective. Thus, it has been tested empirically through a Structural Equation Model. Analysis reveals a strong and positive influence of some dimensions of the relationships with significant others on the psychological wellbeing, specifically team effort, coach closeness and parental learning climate. Following ANOVA shows that élite players perceive significantly better relationships than sub-élite and amateurs and have significantly higher levels of PWB. Those results provide a first evidence for the importance of relationships within and outside sport for an effective talent development, since they positively influence players’ PWB, that is higher in higher competitive level players. It emerges the necessity to further investigate different aspects of psychological wellbeing and to deepen the knowledge about the meaning of relationship in developmental athletes according to a psychosocial approach.